BERHAJI DENGAN DANA KREDIT (KAJI ULANG KONSEP ISTITHA‘AH DALAM HAJI) - H. Rajab (TAHKIM, 2022)
Hajj obligation is associated with the capability (istitha'ah) to practice it, both physically and property. Istitha'ah concept in the implementation of Hajj seems still not agreed on its definition and boundary by Islamic scholars. Therefore, this istitha'ah requirement is understood differently by the muslim. In one hand, many communities do not care about this istitha'ah requirement. They do everything that they can carrying out one of this Islamic pillars, such as saving, selling or mortgaging valuable property, and Hajj gathering. Even in part willing to owe to others, or take credit to the bank for the sake of realizing his desire to hajj at the Baitullah. On the other hand, the istitha'ah requirement is understood that this Hajj obligation is not too urgent, even if doing the hajj is the Islamic pillar. In this regard using the credit funds from the bank to cost the Hajj could be categorized as the capability. Because it is permissible, and their Hajj worship is legitimate according to some Islamic scholars.